Lottery ticket and instant win ticket gambling: exploring the distinctions - Short, Megan; Penney, Alexander; Mazmanian, Dwight; Jamieson, John (My University, 2015)
Lottery gambling is the most common form of gambling in Canada, and lottery tickets and instant win tickets are the most frequently played games. Differences between lottery ticket gambling and instant win ticket gambling were examined by using a large-scale Canadian data set (N = 25,780). Lottery ticket gambling was associated with being older, male, and married, whereas instant win ticket gambling was associated with lower levels of education. Frequency of instant win ticket gambling predicted greater problem gambling severity and participating in more gambling activities independent of demographic variables and lottery ticket gambling. In comparison, frequency of lottery ticket gambling did not predict problem gambling severity or the number of gambling activities independent of demographic variables and instant win ticket gambling. Neither lottery game was related to mental health disorders or substance use. These findings provide converging evidence suggesting that different lottery games may attract distinct types of Canadian gamblers.
Keywords: lottery ticket gambling; instant win ticket gambling; Canada